Training on Arduino Uno-based Smart Home Installation at SMK Al Falah Dago - Anwari, Sabat; Sawitri, Kania; Rustamaji, Rustamaji; Lidyawati, Lita; Siswanto, Wahyu Dwi; Ramdhani, Teguh; Latif, Mochamad Fazri Abdul (Institut Teknologi Nasional, Bandung, 2025)
Understanding smart home technology is increasingly important as automation and IoT become integral parts of modern living and industry. Arduino is a microcontroller that is widely used in practical technology applications, including smart home technology. Smart home systems are computer-based systems that provide comfort, safety, security, and energy savings automatically. They can be programmed via a computer connected to the internet and can manage electrical equipment that can be controlled, monitored, or accessed remotely. To connect Arduino to the internet, the ESP8266 is used. The ESP8266 is a low-cost Wi-Fi microchip with built-in TCP/IP networking software and microcontroller capability. The Arduino system for education and learning at SMK Al Falah Dago is based on an ESP8266 microcontroller embedded in the Arduino Uno Smart Home Installation for connecting to cellphones, relays, lights, and fans as controlled electronic devices. SMK AL Falah Dago is a vocational high school that offers a program in electrical engineering scope, so this training is crucial to equip students with the necessary expertise to design, install, and maintain smart home systems, preparing them to meet the demands of the evolving technological landscape.